2013
DOI: 10.1161/circulationaha.113.002767
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Dilated Cardiomyopathy Diagnosed During Childhood

Abstract: Epidemiological studies from the National Australian Childhood Cardiomyopathy Study (NACCS) and the North American Pediatric Cardiomyopathy Registry (PCMR) determined the incidence of newly diagnosed DCM to be between 0.57 cases per 100 000 population per year for children 0 to 18 years of age 5 and 0.73 cases per 100 000 population per year for ages 0 to 10 years of age. 1 In particular, the registries demonstrated a higher incidence in infants and Australian indigenous and black populations. 5,6 In these stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
71
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(79 citation statements)
references
References 46 publications
4
71
0
4
Order By: Relevance
“…In the American Paediatric Cardiomyopathy Registry, children with neuromuscular disease seemed to have higher mortality rates, mainly due to a lower rate of transplants 19. Some authors have suggested that older children, over the age of five years, may have a lower rate of transplant‐free survival 17, and it has also been suggested that the rate of recovery is higher in younger children 19, 20, 21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the American Paediatric Cardiomyopathy Registry, children with neuromuscular disease seemed to have higher mortality rates, mainly due to a lower rate of transplants 19. Some authors have suggested that older children, over the age of five years, may have a lower rate of transplant‐free survival 17, and it has also been suggested that the rate of recovery is higher in younger children 19, 20, 21.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in agreement with the study by Alexander et al. 20, who reported familiar or genetic cardiomyopathy in 27% of children with DCM. Other studies have suggested that this can occur up to 50% of all cases 17, 25.…”
Section: Discussionmentioning
confidence: 99%
“…Since our original study, follow‐up of patient cohorts from the Australian Childhood Cardiomyopathy Study and the American Pediatric Cardiomyopathy Registry have now provided valuable data about longer‐term outcomes for specific diagnostic groups 6, 7. This UK and Ireland National cohort differs in that it was selected to look at outcomes of symptomatic new‐onset heart failure in children, rather than cardiomyopathy per se .…”
Section: Discussionmentioning
confidence: 99%
“…Results from the Australian Cardiomyopathy in Childhood Study showed that outcome for familial cases of dilated cardiomyopathy was worse than non‐familial cases, but other studies have shown no difference between these two groups 6, 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation